Implementasi Model Pembelajaran Inquiry Training Berbasis Modul Digital Dalam Mempengaruhi Hasil Belajar Siswa - Muhammad Indra; Syaiful Bahri; Ade Evi Fatimah; Harry Pratama Figna; Ryan Dhika Priyatna (PT. INOVASI TEKNOLOGI KOMPUTER, 2023)
The research method used in this study is a quantitative method with a quasi-experimental design, and the sampling technique employed is Stratified Random Sampling. The research sample consists of students from class X TKRO-1 as the experimental group and class X TKRO-2 as the control group, with 32 students in each group. The experimental group received treatment in the form of inquiry training-based learning using digital modules, while the control group underwent conventional learning. The research instrument used in this study was a multiple-choice test consisting of 20 items with 5 answer choices. The results of the study showed that the average score of the experimental group was 81.09, while the average score of the control group was 70.63. Significance testing with a significance level of α 0.05 (5%) indicated that the obtained t-test value was significant (2-tailed), which was 0.00, with the students' learning outcomes being less than 0.05. Therefore, Ha was accepted, indicating a significant difference in mathematical ability between students who applied the inquiry training learning model and those who applied the conventional learning model